2020
DOI: 10.3390/biomedicines8040084
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Induces Apoptosis as a TRAIL Sensitizer via Activation of Caspase 8 and Death Receptor 5 in Human Colon Cancer Cells

Abstract: Though epigallocatechin-3-gallate (EGCG), a major compound of green tea, has anti-diabetes, anti-obesity, anti-inflammatory, and antitumor effects, the underlying antitumor molecular mechanism of EGCG was not fully understood so far. Here the sensitizing effect of EGCG to tumor-necrosis-factor-related apoptosis-inducing ligand (TRAIL) was examined in colorectal cancers. Cotreatment of EGCG and TRAIL synergistically enhanced cytotoxicity and sub G1 accumulation, increased the number of terminal deoxynucleotidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Accordingly, many cancer cells present low levels of death receptors which may trigger apoptosis by interacting with the TNF-related apoptosis-inducing ligand (TRAIL). Co-treatment with EGCG and TRAIL, of highly aggressive colon cancer cells, synergistically increased cytotoxicity, by upregulation of death receptors DR5 and activation of caspase 8 [ 44 ], demonstrating that EGCG can be a potent TRAIL sensitizer.…”
Section: Epigallocatechin Gallate: Origin and Application In Cancer R...mentioning
confidence: 99%
“…Accordingly, many cancer cells present low levels of death receptors which may trigger apoptosis by interacting with the TNF-related apoptosis-inducing ligand (TRAIL). Co-treatment with EGCG and TRAIL, of highly aggressive colon cancer cells, synergistically increased cytotoxicity, by upregulation of death receptors DR5 and activation of caspase 8 [ 44 ], demonstrating that EGCG can be a potent TRAIL sensitizer.…”
Section: Epigallocatechin Gallate: Origin and Application In Cancer R...mentioning
confidence: 99%
“…EGCG is the most abundant polyphenolic compound in dried green tea leaf extracts. Previous studies have reported that EGCG inhibits cell proliferation, metastasis and invasion, and also promotes apoptosis in various cancer cell types [27,29,45,46]. Another study revealed the anti‐metastatic effect of EGCG in the liver metastasis of human CRC [47].…”
Section: Discussionmentioning
confidence: 99%
“…In another example, the synergistic effect of EGCG and TRAIL (tumor necrosis factor (TNF)-induced apoptosis-inducing ligand), a cell death protein, enhances the activity of both caspase 8 and death receptor 5, resulting in the death of colon-cancer cells SW480 and HCT116 [ 95 ].…”
Section: Polyphenolsmentioning
confidence: 99%